The degree of the practice of female leaders in public schools in Al-Delam governorate of the entrance to re-engineering administrative processes in light of the Kingdom of Saudi Arabia 2030 vision - Qaralleh, Thikryat Jibril Obied (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree of the practice of female leaders in public schools in Al-Delam governorate of the entrance to re-engineering administrative processes in light of the Kingdom of Saudi Arabia 2030 vision; to achieve the aims of the study, the descriptive analytical approach was used, and the questionnaire was used as a study tool applied to the study sample consisting of (640) agents and teachers from all schools in Al-Dilam Governorate in the Kingdom of Saudi Arabia, where the study sample was represented by ( 24%) of the total population, and the study reached a number of results, the most important of which were: The results showed that the general arithmetic average of the respondents ’answers to the paragraphs that measure the degree of the practice of female leaders of public school in Al-Dilam Governorate of the entrance to administrative re-engineering“ Hindarah ”has reached (3.51) and represents an average degree of appreciation The results indicated that there were no statistically significant differences between the values ​​of the arithmetic mean for the responses of the sample individuals towards the study tool paragraphs related to the degree of leadership practice for the entrance to re-engineering administrative processes according to the job variable on the tool as a whole and on the sub-dimensions, and the results also showed and there were statistically significant differences in the opinions of the respondents on the practice of female leaders in the approach to re-engineering administrative processes according to the variable of experience on the tool as a whole and on the sub-domains (planning, organization, and communications) and the differences were in favor of the category (less than 5 years) at the expense of the two categories (from 5-less), (10 years) and (10 years or more).